Universities and regional engagement: From the exceptional to the everyday - Tatiana Iakovleva; Elisa Thomas; Laila Nordstrand Berg; Rómulo Pinheiro; Paul Benneworth (Routledge, 2022)
The study of universities' role in regional engagement has traditionally been focusing on exceptional cases. This book presents a reconceptualization which embraces its underlying complexity and proposes a roadmap for a renewed research agenda. Starting from the grassroots level of universities' "everyday" engagements, the book delves into the manifold ways in which university knowledge agents build connections with regional partners. Through 11 empirical chapters, the authors not only chart the diversity among case institutions, engagement mechanisms, and regional contexts but also use that diversity to advance a novel conceptual framework, centered on the process of mundaneness, for unpacking university-regions' everyday activities, taking into account the dynamic, complex, and co-evolving interplay between (a) key social agents and institutions, (b) the contexts in which they are embedded, as well as (c) the historical trajectories and strategic ambitions underpinning context-specific social arrangements and interactions that are mediated by temporal and spatial dimensions. Drawing on evolutionary economic geography, innovation studies, management and organization studies, and historical perspectives, the volume advances a new mode of understanding university-regional engagement as a form of extendable temporary coupling, which also helps to address perennial policy and managerial questions alike of what to do with universities that do not serve local labour market needs and/or are located in regions suffering from brain drain. The book illustrates such dynamics from diverse national contexts and three continents: Brazil, Caribbean, China, Italy, Norway, and Poland. This book will be valuable reading for advanced students, researchers, and policymakers working in economic geography, regional development, innovation, and higher education management.
Keywords: 300; university engagement; regional engagement; academic engagement; industry engagement; higher education; regional development; economic geography